2014
DOI: 10.1021/cs501169t
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Based MOFs for Photocatalytic CO2 Reduction: Role of Coordination Unsaturated Sites and Dual Excitation Pathways

Abstract: The utilization of solar energy for the conversion of CO2 into valuable organic products is one of the best solutions to solve the problems of global warming and energy shortage. The development of photocatalysts capable of reducing CO2 under visible light, especially those containing earth-abundant metals, is significant. Herein we report that a series of earth-abundant Fe-containing MOFs (MIL-101­(Fe), MIL-53­(Fe), MIL-88B­(Fe)) show photocatalytic activity for CO2 reduction to give formate under visible lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
411
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 753 publications
(450 citation statements)
references
References 72 publications
6
411
0
7
Order By: Relevance
“…293 µmolg -1 h -1 was observed. The formation of formic acid during photocatalytic reduction of CO 2 has been reported in literature [41][42][43][44] as well as the photocatalytic splitting of formic acid to H 2 and CO 2 has also been explored [45][46]. Here the photocatalytic splitting of formic acid was performed to confirm that hydrogen generation proceeds as a result of photocatalytic splitting of formic acid/formates formed during the CO 2 reduction and which is also a concomitant to CO 2 reduction to CO (SI Fig.…”
Section: Photocatalytic Activitymentioning
confidence: 84%
“…293 µmolg -1 h -1 was observed. The formation of formic acid during photocatalytic reduction of CO 2 has been reported in literature [41][42][43][44] as well as the photocatalytic splitting of formic acid to H 2 and CO 2 has also been explored [45][46]. Here the photocatalytic splitting of formic acid was performed to confirm that hydrogen generation proceeds as a result of photocatalytic splitting of formic acid/formates formed during the CO 2 reduction and which is also a concomitant to CO 2 reduction to CO (SI Fig.…”
Section: Photocatalytic Activitymentioning
confidence: 84%
“…Interestingly, MOFs are also a class of potential semiconductors [257], which could be also directly applied in the photocatalytic CO 2 reduction as photocatalysts [258][259][260][261]. For example, Fu et al [259] reported that a photoactive Ti-containing metal-organic framework, NH 2 -MIL-125(Ti), exhibited a good photocatalytic activity for reduction of CO 2 to formate anion under visible light irradiation.…”
Section: Increased Surface Area For Co 2 Adsorptionmentioning
confidence: 99%
“…The resemblance between MOFs and bulk transition metal oxides encouraged more than a decade ago the first examples of photocatalytic MOFs. [11][12][13][14][15] Since then, frameworks based on Ti, [16][17][18] Zr, [19][20][21][22][23][24] Fe, 25,26 etc. have been reported for different artificial photosynthetic reactions (i.e.…”
Section: Introductionmentioning
confidence: 99%